(1027) Scope of Application of Quantitative Analysis in Oil Industry نطاق تطبيق التحليل الكمي في صناعة النفط - Mohamed Ali Nassar; Salah Ibrahim El- Dessouki. (INP, 2024)
The scope of quantitative analysis in the oil industry encompasses all phases, from exploration to the marketing of refined products. This has helped minimize contradictions between different managerial levels and promoted the rational utilization of national resources. The oil industry is vast and multifaceted, with this technique witnessing global applications. In France, operations research and numerical analysis were developed for scheduling oil and gas production. In the USSR, quantitative analysis was employed to select technology and determine production assortments in refineries. In Egypt, the Institute of National Planning has implemented various applications, including short-term sales forecasting for the petrochemical industry, applying linear programming for planning production, exporting, and importing in the oil sector, and rationalizing natural gas utilization.